Thor : tales of Asgard,. The boyhood of Thor! - Lee, Stan. 1922-2018 (Spotlight, a division of the ABDO Group, 2014)
"An adaptation, in graphic novel form, of comic books revealing the adventures of the Norse gods and Thor before he came to Earth, featuring the godling Thor's attempts to prove himself to his father, Odin"--Publisher.